PENGARUH CASH HOLDING, BONUS PLAN, REPUTASI AUDITOR, PROFITABILITAS DAN LEVERAGE PADA INCOME SMOOTHING - Natalie, Nancy; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2016)
This study aimed to get empirical evidence about the effect of holding cash, the bonus plan, the auditor's reputation, profitability and leverage on income smoothing. This research was conducted on the property and real estate companies listed on the Indonesian Stock Exchange from 2012 to 2014 year. Based on purposive sampling techniques acquired 25 companies chosen for the research sample, so the total number of observations with the 3-year study period was 75 observational data. Income smoothing Eckel index predicted by logistic regression analysis techniques. Based on the analysis, found that the variable cash holding positive effect on income smoothing, while the profitability variable negative effect on income smoothing. Other variables that the bonus plan, the auditor's reputation and leverage no effect on income smoothing, but has tended positive direction.
Keywords: Income Smoothing, Cash Holding, Bonus Plan, Reputation Auditor, Profitability, Leverage